Metformin Reduces Lipotoxicity-Induced Meta-Inflammation in β-Cells through the Activation of GPR40-PLC-IP3 Pathway. (19th December 2019) - Shen, Ximei; Fan, Beibei; Hu, Xin; Luo, Liufen; Yan, Yuanli; Yang, Liyong
Abstract : Background and Purpose . Metformin, a widely used antidiabetic drug, has been shown to have anti-inflammatory properties; nevertheless, its influence on β -cell meta-inflammation remains unclear. The following study investigated the effects of metformin on meta-inflammatory in β -cells and whether the underlying mechanisms were associated with the G protein-coupled receptor 40-phospholipase C-inositol 1, 4, 5-trisphosphate (GPR40-PLC-IP3) pathway. Materials and Methods . Lipotoxicity-induced β -cells and the high-fat diet-induced obese rat model were used in the study. Results . Metformin-reduced lipotoxicity-induced β -cell meta-inflammatory injury was associated with the expression of GPR40. GPR40 was involved in metformin reversing metabolic inflammation key marker TLR4 activation-mediated β -cell injury. Furthermore, downstream signaling protein PLC-IP3 of GPR40 was involved in the protective effect of metformin on meta-inflammation, and the above process of metformin was partially regulated by AMPK activity. In addition, the anti-inflammatory effects of metformin were observed in obese rats. Conclusion . Metformin can reduce lipotoxicity-induced meta-inflammation in β -cells through the regulation of the GPR40-PLC-IP3 pathway and partially via the regulation of AMPK activity.